Model Dakwah Tarbawi Berbasis Pembiasaan Ibadah dalam Meningkatkan Kecerdasan Spiritual Siswa di Kabupaten Bogor - Kurnia, Yusnia (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2015)
The purpose of this study is to determine the religious program with worship habituation techniques, the implementation of islamic guidance with worship habituation techniques in increasing students' spiritual quotient and to find out the success of implementing islamic guidance with worship habituation techniques in increasing students' spiritual quotient at MTs N 4 Bogor. This study uses a qualitative descriptive method because the problem under study will be described in a structured and objective manner by describing the real situation, the data collection techniques used are observation, interviews and documentation. The results of islamic guidance with worship habituation techniques in increasing students' spiritual intelligence at MTs N 4 Bogor are the emergence of aspects of spiritual quotient in students such as students diligently carrying out obligatory prayers and sunnah prayers, students are accustomed to good behavior, good at being grateful, can imitate the attitude of the Prophet SAW, and have a high sense of solidarity. So it can be concluded that islamic guidance with worship habituation techniques at MTs N4 Bogor has a very large contribution in increasing students' spiritual quotient.